Representasi Budaya Sulang-Sulang Pahompu dalam Film Ngeri-Ngeri Sedap (Analisis Semiotika John Fiske) - Shafinas, Citra Ayu; Santoso, Hudi; Saleh, Amiruddin; Pranata, Rici Tri Harpin (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study aims to analyze the representation of the Sulang-Sulang Pahompu culture in the film Ngeri-Ngeri Sedap through John Fiske’s semiotic approach. The film is significant as it presents the life of the Batak community, rich with traditional values and unique kinship relations. Sulang-Sulang Pahompu, a traditional ritual that emphasizes respect for ancestors and family unity, is depicted through various visual and narrative elements within the film. This research applies Fiske's semiotic analysis method, focusing on three primary codes: social, technical, and ideological, to understand how this ritual is represented and interpreted within the Batak cultural context. The findings reveal that Ngeri-Ngeri Sedap successfully represents Batak cultural symbols by portraying intergenerational conflicts that balance modernization with reverence for ancestral traditions. The film serves not only as entertainment but also as an educational tool that introduces and reinforces Batak cultural identity, encouraging viewers to appreciate and understand local culture. The implications of this study show that film, as a popular medium, can play a significant role in preserving and introducing traditional culture to a broader audience in the era of globalization.